Effect of regional nerve block on tourniquet-related injury in pediatric patients undergoing lower limb surgery: a randomized controlled study - Qin Xia; Rui Chen; Chao Lin; Bohan Zhang; Liuyan Zhou; Jingnan Xiong; Zhou Lv; Yanfei Mao; Rongrong Ren (Annals of Medicine)
Background The efficacy of regional nerve block for pain management has garnered considerable attention. However, few studies have explored their effectiveness in mitigating tourniquet-related injuries and promoting functional recovery in lower limb surgery patients.Methods : Sixty-four pediatric patients aged 6–12 undergoing knee arthroscopic surgery under general anesthesia. All patients were randomized to receive either femoral nerve block combined with sciatic nerve block (the PNB group) or standard general anesthesia only (the control group). The primary endpoint was the incidence of tourniquet-induced hypertension. Secondary endpoints included the cumulative oral morphine equivalent consumption within 24 h post-surgery, the perioperative pain intensity, inflammation and oxidative stress levels (assessed via IL-6, IL-10, SOD, and MDA), plasma levels of circulating adipokines (FABP-4 and Apelin-13), time to first ambulation, and hospital stay duration.Results The PNB group showed a lower incidence of tourniquet-induced hypertension compared with the control group (33.33% vs 73.33%, relative risk [95% confidence interval] of 0.182 [0.06–0.55]; p = 0.004). Patients in the PNB group demonstrated a 39% reduction in oral morphine equivalent consumption at 24 h postoperatively (p < 0.001). In comparison to the control group, the PNB group also exhibited reduced postoperative pain intensity, inflammation, and oxidative stress levels, as well as lower blood glucose fluctuation. Additionally, patients in the PNB group had a significantly shorter time to first ambulation and a shorter hospital length of stay.Conclusions The present study demonstrated that combining femoral nerve block and sciatic nerve block can alleviate tourniquet-related injuries, decrease opioid consumption, facilitate a quicker and less painful recovery period.